A comparative life cycle assessment (LCA) of lighting technologies for greenhouse crop production. (1st January 2017) - Zhang, Hao; Burr, John; Zhao, Fu
Abstract: Greenhouse, indoor or vertical horticulture using supplemental lighting have become an important part of specialty crop cultivation. This study reports a comparative life cycle assessment of different lighting systems applied in greenhouse crop production. Two typical cases are considered: (1) 1000 W HPS lighting system vs. 650 W LED lighting system with functional unit defined as 653 kg tomatoes from 8 sq. ft. floor area over 15 year; (2) 150 W incandescent lighting vs. 18 W LED lighting with functional unit defined as 1640 sq. ft. of bedding plants from 8 sq. ft. floor area over 15 year. Impact assessment is done using TRACI methodology and cumulative energy demand (CED) is also considered. The results show that 650 W LED lighting system has smaller environmental impact than the HPS lighting system (38%–47% reduction). The use phase dominates the total environmental impacts (approximately 74%–97% for HPS lighting system, and 78%–100% for LEDs). Benefits of substituting LEDs for incandescent lighting for greenhouse applications are even larger leading to a significant reduction (67%–90%) on most environmental impact categories considered (except carcinogenics where LED is 12% higher)). For this case, the use phase remains the largest contributor, accounting for 28%–100% for incandescent and 47%–100% for LEDs.